PERAN PACALANG DAN DAMPAKNYA PADA MASA PANDEMI COVID-19 DI BANJAR ADAT DESA DINAS PEMECUTAN KELOD - Sri Wiguna, Ni Made Melin; Suka Arjawa, I Gusti Putu Bagus; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
study analyzed the role of pacalang in addition to the role in maintaining customary security but also played an active role during the Covid-19 pandemic in Banjar Adat Village Kelod Disarmament Service. The approach used in this study is qualitative with the analysis that uses the functional structural theory of Robert King Merton. That there is a manifet function of pacalang is to maintain security at the time of the traditional and cultural activities of hindu communities in Bali. While the latent function of the role of pacalang in the Covid-19 pandemic an active role in the role of socializing, educating, prevention and supervision role of the pacalang, namely the decrease in Covid-19 cases in Kelod Village, pacalang gaining experience. Meanwhile, the negative impact of pacalang involvement is that pacalang can be conflicts within the family and conflicts .